The influence of pedaling frequency on blood lactate accumulation in cycling sprints - Haase, R.; Dunst, A. K.; Nitzsche, N. (International Journal of Sports Medicine, 2024)
Anaerobic performance diagnostics in athletes relies on accurate measurements of blood lactate concentration and the calculation of blood lactate accumulation resulting from glycolytic processes. In this study, we investigated the impact of pedaling frequency on blood lactate accumulation during 10-second maximal isokinetic cycling sprints. Thirteen trained males completed five 10-second maximal isokinetic cycling sprints on a bicycle ergometer at different pedaling frequencies (90 rpm, 110 rpm, 130 rpm, 150 rpm, 170 rpm) with continuous power and frequency measurement. Capillary blood samples were taken pre-exercise and up to 30 minutes post-exercise to determine the maximum blood lactate concentration.